PENGARUH MEROKOK TERHADAP LAJU ALIRAN SALIVA - Lisma Yendri; Surya Nelis; Yustini Alioes (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2018)
TITLETHE EFFECT OF SMOKING TO SALIVARY FLOW RATEABSTRACTSmoking is a habbit which is commonly found and it is the biggest threat for future world’s health. Nicotine is toxic components that is the most widely contained in cigarette. Prolonged exposure to nicotine on salivary gland is a causative factor of pathological processes or morphological and functional abnormalities of salivary gland, especially acinar cells and myoepithelial cells. The purpose of research to know the representation salivary flow rate smokers and the influence of smoking duration and number of cigarettes which are smoked to the salivary flow rate. This study was an analytical survey with cross sectional design. Total samples 90 persons were taken proportionally and divide into 9 criteria. Collecting unstimulated salivary used spitting method. Data analysis used the krusskal-wallis test and pos hoc mann-whitney.The mean (SD±) salivary flow rate were 0,36 (±0,207) ml/min in smokers and krusskal-wallis test to looked the influences of salivary flow rate showed a value of p 0,05 (p=0,012). The study showed that there were significant influence between smoking duration and number of cigarettes which are smoked with the salivary flow rate.